The Fungal Iron Chelator Desferricoprogen Inhibits Atherosclerotic Plaque Formation - Potor, László (Int J Mol Sci, 2020)
Hemoglobin, heme and iron are implicated in the progression of atherosclerosis. Therefore, we investigated whether the hydrophobic fungal iron chelator siderophore, desferricoprogen (DFC) inhibits atherosclerosis. DFC reduced atherosclerotic plaque formation in ApoE(−/−) mice on an atherogenic diet. It lowered the plasma level of oxidized LDL (oxLDL) and inhibited lipid peroxidation in aortic roots. The elevated collagen/elastin content and enhanced expression of adhesion molecule VCAM-1 were decreased. DFC diminished oxidation of Low-density Lipoprotein (LDL) and plaque lipids catalyzed by heme or hemoglobin. Formation of foam cells, uptake of oxLDL by macrophages, upregulation of CD36 and increased expression of TNF-α were reduced by DFC in macrophages. TNF-triggered endothelial cell activation (vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecules (ICAMs), E-selectin) and increased adhesion of monocytes to endothelium were attenuated. The increased endothelial permeability and intracellular gap formation provoked by TNF-α was also prevented by DFC. DFC acted as a cytoprotectant in endothelial cells and macrophages challenged with a lethal dose of oxLDL and lowered the expression of stress-responsive heme oxygenase-1 as sublethal dose was employed. Saturation of desferrisiderophore with iron led to the loss of the beneficial effects. We demonstrated that DFC accumulated within the atheromas of the aorta in ApoE(−/−) mice. DFC represents a novel therapeutic approach to control the progression of atherosclerosis.